Agile Manufacturing: Building Flexibility in Operational Management - Imam Wibowo (Paspama Institute, 2023)
This research aims to investigate the application of the Agile Manufacturing approach in the context of operational management and how it can help organizations increase their flexibility in facing dynamic changes in the business environment. This research methodology includes a literature study to understand the concept of Agile manufacturing using a qualitative descriptive approach. The research results show that the integration of agile manufacturing, lean manufacturing, digital technology and employee development concepts has a positive impact in building adaptive and efficient operational management. Research findings confirm that the combination of lean principles with an agile manufacturing approach creates a solid foundation for responsibility for change and operational risk management. The use of digital technology is proven to provide greater visibility into the supply chain, facilitate real-time monitoring and speed up decision making. In addition, employee development has proven to be a key factor in improving individual skills and establishing a company culture that supports adaptability.